Assuming the equation is:
![(x)/(2)-(10x-25)/(10)=3(x+3)-(x-14)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zp6bt8mz4xwuzn501sqc4884ofdejmxpyf.png)
When fractions involve numeric denominators, the fractions can be removed by multiplying (both sides) by the LCM of the denominators.
Here the denominators are 2 and 10, hence the LCM is 10.
Multiply by 10 on both sides, not forgetting to distribute when multiplying on the right side:
![10(x)/(2)-10(10x-25)/(10)=10*3(x+3)-10(x-14)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/cqrbepcj2oxms0mg4etdnp4b9j9ghurs0h.png)
simplify, remember that there are always implied parentheses around numerators and denominators:
![5x-(10x-25)=30(x+3)-10(x-14)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/a8uncre9mcjq1b1qaf782uowku558w92eg.png)
Now, distribute, i.e. remove parentheses and distribute:
5x-10x+25=30x+90-10x+140
Simplify
-5x+25=20x+230
transpose terms
25-230=20x+5x
solve
x=-205/25=-41/5
In this particular case, we can also take advantage of the term
(10x-25)/10=5(2x-5)/10=(2x-5)/2 which greatly simplifies the solution process, because the LCM will then be 2 instead of 10.
If we do that, the solution will be:
Multiply by 2 on both sides, not forgetting to distribute when multiplying on the right side:
![(x)/(2)-(10x-25)/(10)=3(x+3)-(x-14)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zp6bt8mz4xwuzn501sqc4884ofdejmxpyf.png)
simplify, remember that there are always implied parentheses around numerators and denominators:
![2(x)/(2)-2(2x-5)/(2)=2*3(x+3)-2(x-14)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/n37v2nebujlirzzoimdxgxx5ppax5u478x.png)
![x-(2x-5)=6(x+3)-2(x-14)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9n71a26nvv56fc9d3g5yfd2fatboywwwoo.png)
Now, distribute, i.e. remove parentheses and distribute:
![x-2x+5=6x+18-2x+28](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vrsfskxd1lc8rv7zp8qrh1bob0pqh2mvvu.png)
Simplify
-x+5=4x+46
solve
5-46=4x+x
-41=5x
x=-41/5
with the same results.